Ascorbic Acid and Carotenoid Contents in Tomato Callus: Effects of Explant Source and Subculture - Imam Purwanto; Yulita Nurchayati; Erma Prihastanti (Biology, Medicine, & Natural Product Chemistry, 2026)
The production of natural compounds in tomato can be achieved through callus culture by selecting the most suitable explant. The objectives of this study were to examine the effects of explant source and culture maintenance on the growth, ascorbic acid content, and carotenoid content of tomato callus. Callus induction was carried out on MS medium supplemented with 2,4-D. The resulting calli were divided into two groups: one subcultured into fresh medium and the other maintained without subculture. The study design used a completely randomized design of two factors, they were explants source (cotyledons, hypocotyls and root sprouts) and subculture treatment. The observed parameters were growth of callus, carotenoid and ascorbic acid content analized by spectrophotometer. The results showed that the highest callus weight (0.29 g) was obtained from hypocotyl explants. Subculture treatment significantly affected ascorbic acid content but did not influence carotenoid content. Callus from cotyledon explants produced the highest ascorbic acid content (15.2 g/100 g). Subculture treatment increased callus fresh weight, carotenoid content, and ascorbic acid content compared to the non-subculture treatment. In conclusion, hypocotyls were the best explant source for increasing biomass, while cotyledons were the most effective for enhancing ascorbic acid production.